ANALISIS SISTEM ANTRIAN BONGKAR MUAT PETI KEMAS DI PT. XYZ DENGAN TEORI ANTRIAN DAN SIMULASI - Mohammad Bani Adi (2020)
PT. XYZ is a company that engaged in the logistics services industry. The company provides container loading and unloading services, temporary goods storage and inspection of goods that arrive at port and pass through customs. Of the many containers that are available, container queues often occur because there is only one container loading and unloading station. There are 2 types of containers that come every day, namely partner and non-partner containers. This study conducted a study of the queue system for arrival of partner containers at the receiving work station at PT. XYZ by using queuing theory and model simulation methods. It is known that the company queue type is Single Channel Single Phase with First Come First Serve services. Initial observations were carried out for three days in the period of 5 November 2019 to 7 November 2019. The initial modeling followed the actual queuing process with one work station and found that the container has an average waiting time of 52 minutes / container and with the addition of 2 work stations to be 3 work stations results in a shorter average waiting time of 7.01 minutes / container. With a total waiting time efficiency of 86.6%.